Answers

2014-06-25T12:57:52+05:30
6√12÷√3×3√2
=6
×3.4641÷1.7320×3(1.4142)
=20.7846÷7.3481
=2.8287
                                                OR
\frac{6 \sqrt{2}* \sqrt{2}* \sqrt{3} }{ \sqrt{3}* \sqrt{2}*3 } = \frac{6 \sqrt{2} }{3} 
-------[since √3 and √2 get cancelled out].
0
mark my ans bst plzzzzzzzz
6√12÷√3×3√2 = 6x (√4x3) / √3 x 3√2
=6x2√3 / √3 x 3√2
= 4 / √2
=2√2
2014-06-25T18:27:18+05:30
6√12÷√3×3√2 = 6x (√4x3) / √3 x 3√2
                           =6x2√3 / √3 x 3√2
                           = 4 / √2
                           =2√2
0